MEDIA LINGKUNGAN ALAM TERHADAP KOGNITIF ANAK AUTIS - APRIANTI, ERNA (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   The development of cognitif ability is aimed to help children to comprehend the lesson. Learning of knowing colours can be done by using natural enviromen media. Natural enviroment media is all thing derived from nature. The enviromen media means planst that produce natural dyes. This research has  an aim to prove effect of natural enviroment media to cognitif ability of autistic children at educational foundation mutiara hati mojokerto. This methode or research used quantitatif approach. Data were collectid by using test and documentations. Test were administratered to autistic children before and after treatment while documentations as supporting data or prove that research was actually conducted. Result of the research was actually conducted. Result of the research indicated that on the pre tests the everage value was 24, 96 and after treatment or post test was 70,91. This indicates that there are significant changes. Score zh=2,20>zt = 1,96 it could be concluded that ho is rejected and ha is accepted so there is effect of natural enviroment media to cognitif ability of autism children at mutiara hati educational mojokerto.   Keyword : cognitif, natural enviroment media